2013
DOI: 10.1093/cid/cit799
|View full text |Cite
|
Sign up to set email alerts
|

Telaprevir in the Treatment of Acute Hepatitis C Virus Infection in HIV-Infected Men

Abstract: Incorporating telaprevir into treatment of acute genotype 1 HCV in HIV-infected men halved the treatment duration and increased the SVR rate. Larger studies should be done to confirm these findings. Clinicians should be alert to detect acute HCV infection of HIV-infected men to take advantage of this effective therapy and decrease further transmission in this epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
(51 reference statements)
2
45
1
Order By: Relevance
“…Till date, only one pilot study using Telaprevir with Peg-IFN/RBV for 19 patients with acute HCV/HIV coinfection has been reported, with 84% SVR rate. 164 Results of several studies using all-oral DAA-based regimens are awaited with interest 158 and are expected to change the paradigm for treatment of acute HCV infection.…”
Section: Antiviral Therapy For Ahcv Infectionmentioning
confidence: 99%
“…Till date, only one pilot study using Telaprevir with Peg-IFN/RBV for 19 patients with acute HCV/HIV coinfection has been reported, with 84% SVR rate. 164 Results of several studies using all-oral DAA-based regimens are awaited with interest 158 and are expected to change the paradigm for treatment of acute HCV infection.…”
Section: Antiviral Therapy For Ahcv Infectionmentioning
confidence: 99%
“…Ten studies (83%) originated from Europe [6,38,39,40,41,42,43,44,45,46], mostly from the UK [38,40,41,45,46] and France [6,39,44]. Eight were prospective in study design [6,38,39,41,44,45,47,48]. Most studies [6,38,39,40,43,46,47,48] featured an ITT analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Eight were prospective in study design [6,38,39,41,44,45,47,48]. Most studies [6,38,39,40,43,46,47,48] featured an ITT analysis. One study [46] included 3 patients who were each treated twice for 2 separate a-HCV infections.…”
Section: Resultsmentioning
confidence: 99%
“…The other choice is the addition of protease inhibitor to peg-IFN + ribavirin combination. Data obtained through the New York acute hepatitis C Surveillance Network showed that a 12-week treatment course with a combination of peg-IFN + ribavirin + telaprevir achieved SVR in 84% of 19 human immunodeficiency virus (HIV)-infected men with acute genotype 1 HCV infection (23). SVR was also detected at the rate of 78% with triple combination treatment with boceprevir (BOC) in the similar patient population and SVR rate was reported to be 95% in the group who achieved rapid virologic response (24).…”
Section: Interferon-based Therapiesmentioning
confidence: 99%